Verifikasi Parameter Presipitasi Akumulasi 24 Jam pada Model Cuaca Numerik Tahun 2017-2020 - kiki, Kiki (Megasains, 2021)
The 24-hour accumulated precipitation parameters from four numerical models contained in the Synergie operational tool, namely GFS, IFS, ARPEGE, and WRF, were verified using daily surface observation data at 34 study points representing each province in Indonesia. Three verification methods, namely dichotomy, multi-category, and verification methods for continuous parameters are used to measure the performance of each model in predicting daily rainfall quantity in the period 2017 to 2020. The results show that the IFS model has the best performance in all of the classification done in this study compared to other 3 numerical models. Keywords: Precipitation, Verification, Accuracy